Combining Think Pair Share Model with Digital Media to Enhance Students’ Basic Grammar Mastery: Is It Effective? - Eka Novita Sari; Ardiana Ardiana; Ika Sastrawati (International Journal of English Education and Linguistics (IJoEEL), 2022)
Grammar is an important aspect of learning English and any language. However, for some students, mastering English grammar is considered arduous as it requires students to understand plenty of rules, and this makes them desperate to learn. This study aims to find out whether Think Pair Share method combined with digital media may enhance the students’ grammar mastery at UPT SMPN 1 Binamu. This study was a pre-experimental study where the data was obtained from a basic grammar test. The population in this study were students of class VIII.I at UPT SMPN 1 Binamu for the academic year of 2022/2023. The results showed that the average score of students' grammar mastery consisting of pre-test and post-test, namely Pre-test was 18.75 which was categorized as "Very Poor and Poor" while post-test was 87,25 which is categorized as "Excellent and Very Good". This shows that the average value of the pre-test and post-test increased by 68.5 points. The t-test analysis showed that by applying a significant level of 0.05 with a degree of freedom of 23 and a p-value (sig .2-tailed) is 0.000 indicating that there is a significant difference between the pre-test and post-test results of the students. In other words, the result (sig.2-tailed) of the students' post-test is not greater than the significance level (0.000< 0.05).